(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Field experiment was carried out for two consecutive years to study the effectiveness of soil and foliar application of micronutrients on the yield of tomato (Lycopersicon esculentum Mill.) at the Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur. The micronutrients zinc (Zn) in the form of zinc sulphate (ZnSO4.7H2O) at the rate of 0.05 % and boron (B) in the form of boric acid (H3BO3) at the rate of 0.03% were applied as foliar spray at three different stages of plant growth i.e (i) before flower initiation; (ii) after fruit set when it becomes approximately marble sized; and (iii) at 20 days interval of second spray. The tomato yield and its contributing yield traits were significantly affected by foliar fertilizer treatments as against soil application of B and Zn fertilizers. Among various treatments, foliar application of Zn (0.05 %) + B (0.03%) produced maximum fruit yield (85.5 and 81.7 t ha-1 in 2013 and 2014, respectively) while the control no application of Zn (0.0) and B (0.0) produced 66.8 and 60.7 t ha-1 in 2013 and 2014, respectively and it was statistically identical with soil application of B and Zn @ 2 and 6 kg ha-1 (T5), respectively. The increment of yield was 19.2 to 31.1% and 7.57 to 18.3%, respectively, over control and soil application. The integrated use of foliar application of micronutrients and soil application of macronutrients are recommended to enhance tomato yield. Bangladesh J. Agril. Res. 41(3): 411-418, September 2016